New Directions in Employment Relations Theory: Understanding Fragmentation, Identity, and Legitimacy. (May 2021) - Doellgast, Virginia; Bidwell, Matthew; Colvin, Alexander J. S.
This article introduces the special issue on New Theories in Employment Relations. The authors summarize the history of employment relations theory and reflect on the implications of recent disruptive changes in the economy and society for new theory development. Three sets of changes are identified: the growing complexity of actors in the employment relationship, an increased emphasis on identity as a basis for organizing and extending labor protections, and the growing importance of norms and legitimacy as both a constraint on employer action and a mobilizing tool. The articles in this special issue advance new frameworks to analyze these changes and their implications for the future of employment relations.